Amino terminal domains of the NMDA receptor are organized as local heterodimers. - Chia-Hsueh Lee; Eric Gouaux (PLoS ONE, 2011)
The N-methyl-D-aspartate (NMDA) receptor, an obligate heterotetrameric assembly organized as a dimer of dimers, is typically composed of two glycine-binding GluN1 subunits and two glutamate-binding GluN2 subunits. Despite the crucial role that the NMDA receptor plays in the nervous system, the specific arrangement of subunits within the dimer-of-dimer assemblage is not conclusively known. Here we studied the organization of the amino terminal domain (ATD) of the rat GluN1/GluN2A and GluN1/GluN2B NMDA receptors by cysteine-directed, disulfide bond-mediated cross-linking. We found that GluN1 ATDs and GluN2 ATDs spontaneously formed disulfide bond-mediated dimers after introducing cysteines into the L1 interface of GluN2A or GluN2B ATD. The formation of dimer could be prevented by knocking out endogenous cysteines located near the L1 interface of GluN1. These results indicate that GluN1 and GluN2 ATDs form local heterodimers through the interactions in the L1-L1 interface and further demonstrate a dimer-of-heterodimer arrangement in GluN1/GluN2A and GluN1/GluN2B NMDA receptors.